Organometallic vs organic photoredox catalysts for photocuring reactions in the visible region - Bonardi, Aude-Héloise; Dumur, Frédéric; Noirbent, Guillaume; Lalevée, Jacques; Gigmes, Didier (Beilstein Journal of Organic Chemistry, 2018)
Recent progresses achieved in terms of synthetic procedures allow now the access to polymers of well-defined composition, molecular weight and architecture. Thanks to these recent progresses in polymer engineering, the scope of applications of polymers is far wider than that of any other class of material, ranging from adhesives, coatings, packaging materials, inks, paints, optics, 3D printing, microelectronics or textiles. From a synthetic viewpoint, photoredox catalysis, originally developed for organic chemistry, has recently been applied to the polymer synthesis, constituting a major breakthrough in polymer chemistry. Thanks to the development of photoredox catalysts of polymerization, a drastic reduction of the amount of photoinitiators could be achieved, addressing the toxicity and the extractability issues; high performance initiating abilities are still obtained due to the catalytic approach which regenerates the catalyst. As it is a fast-growing field, this review will be mainly focused on an overview of the recent advances concerning the development of organic and organometallic photoredox catalysts for the photoreticulation of multifunctional monomers for a rapid and efficient access to 3D polymer networks.
Keywords: photoinitiator; photopolymerization; photoredox catalysis; photoredox catalyst